2023
DOI: 10.21203/rs.3.rs-2527927/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real world safety and exploratory efficacy of gene therapy for patients with 5q-Spinal Muscular Atrophy in a Brazilian cohort

Abstract: Spinal muscular atrophy (SMA) is a motor neuron disease associated with progressive muscle weakness, ventilatory failure, and reduced survival. Onasemnogene abeparvoves is the first gene replacement therapy (GT) approved to treat this condition. An observational retrospective study was conducted to assess adverse events and efficacy of GT in SMA patients. Forty-one patients with SMA (24 females, 58.5% and 33 SMA type 1, 80.1%) were included. The mean age at GT dosing was 18 (± 6.4) months. Thirty-six patients … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These real-world studies have confirmed the efficacy of the gene replacement therapy in an expanded age range of patients eligible for treatment, including those up to two years old and also patients with three copies of SMN2 , regardless of the type of SMA. 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 Additionally, some studies have evaluated the use of onasemnogene abeparvovec in patients who had previously been treated with other specific therapies, such as nusinersen or risdiplam. 102 103 105 106 108 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These real-world studies have confirmed the efficacy of the gene replacement therapy in an expanded age range of patients eligible for treatment, including those up to two years old and also patients with three copies of SMN2 , regardless of the type of SMA. 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 Additionally, some studies have evaluated the use of onasemnogene abeparvovec in patients who had previously been treated with other specific therapies, such as nusinersen or risdiplam. 102 103 105 106 108 …”
Section: Resultsmentioning
confidence: 99%
“… 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 Additionally, some studies have evaluated the use of onasemnogene abeparvovec in patients who had previously been treated with other specific therapies, such as nusinersen or risdiplam. 102 103 105 106 108 …”
Section: Resultsmentioning
confidence: 99%